Heterogeneidades e idiossincrasias: Eficiências municipais na saúde básica a partir de gastos com pessoal - Bernardo Alves Furtado (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– Brazil has constitutionally adopted a National Health System (SUS) since 1988. SUS is designed so that central government, states and municipalities together offer public, free for all, full health coverage. The complexity and territorial arrangement of SUS have been developed in such a way that each government body has its specific obligations within the system. This legal framework establishes that the municipalities are competent and responsible for providing basic health attention under general guidance of federal policy. Within this context, the objective of this paper is to estimate levels of efficiency and under which determinants municipalities' personnel expenditures are correlated to increases in health service provision results in the period 2000-2010. In order to do that, firstly, spatial exploratory analysis is applied to data from two different official sources on municipal personnel expenditure. The spatial analysis enables insights into the quality of the expenditure information as well as its heterogeneous spatial distribution. The data used comes from i) municipal data demanded by the National Treasure and Accountancy Justice Department and ii) labor social information compiled by the Ministry of Labor. Secondly, a Data Envelopment Analysis (DEA) is performed to evaluate municipal expenditure against health provision indicators. Finally, a regression is fitted to identify which elements suggested in the literature are the most influential on the technical efficiency for the Brazilian municipalities. [...]
Keywords: H51; H71; C14; 330; municipalities; efficiency; personnel expenditure; spatial analysis; public policy; Brazil